Economic consequences of announcing strategic alternatives: A voluntary disclosure's benefits and costs - Zha Giedt, Jenny (Contemporary Accounting Research, 2023)
Abstract This study examines the benefits and costs to a company of publicly announcing that it is seeking a potential sale or merger. I find that the announcement leads to increased market attention and a more robust merger and acquisition sales process—the benefits of improved transparency. However, I also find evidence of the announcement alienating stakeholders and increasing business disruption—the costs of credible disclosure. I document the countervailing valuation effects of these benefits and costs, where the net valuation effect depends on whether the company is subsequently acquired. This research is important because it (1) demonstrates the disclosure's impact on the company through multiple channels, (2) estimates the valuation effects, and (3) identifies key considerations for investors and other stakeholders who bear the consequences of such a disclosure.